Analisis Isi dan Fungsi Cerita Prosa Rakyat di Kanagarian Koto Besar, Kab Dharmasraya - Andi Purwanto (Universitas Andalas, 2010)
This article describes documentation and collecting phase of Nagari Koto Besar, Dharmasraya West Sumatera folktales. These folktales then analized with Bascom’s function theory. Based on analysis, there are 9 folktales which describes history of Koto Besar. The folktales are Asal Usul Munculnya Koto Besar, Rumah Tuo, Burung Beo dan Koto Besar, Penghormatan terhadap Raja, Sapi yang Dilarang, Orang Bunian, Padi Sebesar Biji Kelapa, Bukik Mayang Taurai, and Sungai Bayie dan Sungai Balun.